Problems of Appointing Party Leaders as State Ministers in the Indonesian Constitutional System - Radytia, Moch (IJBLE Scientific Publications Community Inc., 2024)
Indeed, the stability in running the wheels of government using the presidential system is very promising. However, at present, in Indonesia, the presidential system of government is not maximized, this is because the presidential system of government that is applied has been collaborated with a multi-party system. The application of the system is not maximized as evidenced in the formation of the cabinet, namely the selection of ministers by the president is only used as a forum for